FEATURES OF THE INTERACTION BETWEEN LOCAL GOVERNMENT BODIES AND LAW ENFORCEMENT AUTHORITIES UNDER THE MARTIAL LAW CONDITIONS - Rohozinnikova, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to outline the functions of the Specialized Environmental Prosecutor’s Office as a subject of protection of citizens’ rights to environmental safety. In order to achieve the specified goal, the following tasks were solved: 1) the content of the authorities of the Specialized Environmental Prosecutor’s Office as a subject of protection of citizens’ rights to environmental safety was summarized and revealed; 2) the legal capabilities of the Specialized Environmental Prosecutor’s Office in the specified sphere are outlined. Research methods of the proposed research are determined by its theoretical nature, which defined the appropriateness of general theoretical and analytical research methods. Results: the conducted analysis proves that the norms of the profile Law of Ukraine «On Environmental Protection» and the complex of legal norms of criminal and administrative justice form a sufficient legal basis for the activities of the prosecutor’s office on behalf of the society in protecting public interests and the rights of individuals in matters of environmental safety. It is substantiated that the Specialized Environmental Prosecutor’s Office has every reason to act as a subject of protection of citizens’ rights to environmental safety, including in the context of understanding the subject as a person (organizational and legal institution) that carries out certain activities aimed at the practical transformation of objective reality and is the bearer of certain defined qualities that enable him to perform socially significant functions. Discussion: the thesis is argued that the Specialized Environmental Prosecutor’s Office is an important structural unit in the national system of prosecutor’s offices. Its appearance can be interpreted as recognition of the priority of solving problematic issues of environmental protection. It is claimed that the tasks, powers and functions of the Specialized Environmental Prosecutor’s Office provided by the legislation correspond to European visions for such institutions.